Verbal isolation in Peru - Pozzi-Escot, Inés (1987)
The solitary confinement is an ancient drama in Peru. Garcilaso de la Vega writes in the Royal Comments that the Inca kings "commanded... to learn the general language for two main reasons. One was because they did not have before them as many interpreters as was necessary to understand and respond to so much variety. of languages ​​and nations as there were in their Empire.The Incas wanted their vassals to speak to them mouth to mouth (at least personally and not through third parties) and to hear from theirs the dispatch of their business, because they will achieve the more satisfaction and consolation it gives. the same word said by the Prince, not by the Minister.